2017
DOI: 10.1016/j.disc.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

On path decompositions of2k-regular graphs

Abstract: Tibor Gallai conjectured that the edge set of every connected graph G on n vertices can be partitioned into ⌈n/2⌉ paths. Let G k be the class of all 2k-regular graphs of girth at least 2k − 2 that admit a pair of disjoint perfect matchings. In this work, we show that Gallai's conjecture holds in G k , for every k ≥ 3. Further, we prove that for every graph G in G k on n vertices, there exists a partition of its edge set into n/2 paths of lengths in {2k − 1, 2k, 2k + 1}.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The proof of the next lemma follows the proof of Lemma 3.2 in . Given a cycle C in a graph G, a chord of C is an edge in GE(C) that joins two distinct vertices of C.…”
Section: Reducing Subgraphsmentioning
confidence: 92%
“…The proof of the next lemma follows the proof of Lemma 3.2 in . Given a cycle C in a graph G, a chord of C is an edge in GE(C) that joins two distinct vertices of C.…”
Section: Reducing Subgraphsmentioning
confidence: 92%
“…In 1988, Favaron and Koudier [6] proved that the conjecture holds for graphs where the degree of every vertex is either 2 or 4. More recently, Botler and Jiménez [3] proved that the conjecture holds for 2k-regular graphs of large girth and admitting a pair of disjoint perfect matchings. Jiménez and Wakabayashi [7] showed that the conjecture holds for a subclass of planar, triangle-free graphs satisfying a distance condition on the vertices of odd degree.…”
Section: Introductionmentioning
confidence: 99%
“…, for i ∈ [k] and j ∈ [7]. For each i ∈ [k] and j ∈ [7], we construct a set F P CA i,j of fictive edges as above and let F P CA be the union of these sets.…”
Section: ( † †)mentioning
confidence: 99%